The Strategy to Increase the Regional Revenue (PAD) of the Government of Central Kalimantan through the Governor Regulation No. 16/2018 - Suprayitno Suprayitno; Riamona Sadelman Tulis; Ira Zuraida (Indonesian Association for Public Administration, 2018)
This article aimed to analyze and identify the strategies of Central Kalimantan Provincial Government as an effort to increase Regional revenue (Pendapatan Asli Daerah - PAD) through third-party grants or donations. One of the efforts made by the Central Kalimantan Provincial Government in increasing regional revenue (PAD) is through the issuance of Governor Regulation No. 16/2018 on Guidelines for the Acceptance and Management of Grants or Donations from Third Parties to the Central Kalimantan Provincial Government. The data showed that the governor’s regulation had shown positive results relating to the efforts to increase the Regional revenue in Central Kalimantan Province. Local Revenue Offices of Central Kalimantan as the leading sector to implement the regulation has made several strategic efforts including sharing/spreading the information to 3 P i.e., investors, monitoring and controlling. The purposes of the governor’s regulation No. 16/2018 to provide legal protection to guarantee the participation of third parties in Central Kalimantan development, provide legal certainty in the management and acceptance of third-party grants or donations, and create an orderly administration, transparency and accountability in acceptance the grants or third-party donations to the government of Central Kalimantan Province. The collaboration cooperation between Central Kalimantan Provincial Government and the private sector to increase Regional revenue (PAD) needs to have support from all parties.